Interstitial lung disease in South Africans with systemic sclerosis - Ashmore, Philippa (My University, 2015)
BACKGROUND: Interstitial lung disease (ILD) is one of the leading causes of death in systemic sclerosis (SSc). PATIENTS AND METHODS: A retrospective review of case records, over 20 years, of SSc patients attending a tertiary Connective Tissue Diseases Clinic. Comparisons between ILD and non-ILD groups at presentation were performed in order to identify baseline associations and predictors of ILD. RESULTS: Of the 151 participants that met inclusion criteria, 60 (40%) had ILD. On multivariate analysis the only three variables to remain significant were median duration of disease (OR 1.2 (1.1-1.3); p<0.001), speckled anti-nuclear antibody (ANA) pattern (OR 2.95 (1.22-7.15); p=0.017) and bibasal crackles (OR 5.4 (2.1- 13.5); p<0.0001). Univariate analysis of baseline variables associated with interstitial lung disease in systemic sclerosis. Baseline Variable ILD (n=60) Non-ILD (n=91) OR (CI 95%) p Bibasal crackles (%) 28 (46.7) 10 (11.0) 7.1 (3.1-16.3) <0.0001 Diffuse disease subtype (%) 49 (81.7) 45 (48.9) 4.6 (2.1-9.9) <0.001 Limited disease subtype (%) 8 (13.3) 38 (41.3) 0.2 (0.1-0.5) <0.001 Anti-centromere antibodies (%) 0 (0.0) 10 (13.0) - 0.006 Cough (%) 21 (35.0) 15 (16.5) 2.7 (1.3-5.9) 0.007 Median duration in years (IQR) 6.1 (8.3) 4.0 (5.0) 2.2 (1.8-2.4) 0.009 Speckled ANA pattern (%) 29 (50.9) 25 (32.5) 2.5(1.2-4.9) 0.010 Dyspnoea (%) 27 (45.0) 24 (26.4) 2.3 (1.1-4.6) 0.014 Gold mining history (%) 5 (8.3) 1 (1.1) 8.2 (0.9-71.9) 0.037 ANA=antinuclear antibody; ILD=interstitial lung disease; IQR= interquartile range; OR=odds ratio Additionally, dyspnoea was associated with ILD severity (p=0.008). Bibasal crackles (p=0.014), increased plasma urea (p=0.041), and reduced serum albumin (p=0.007) were associated with mortality in the ILD group. CONCLUSION: Interstitial lung disease in South African SSc patients is common. The diffuse cutaneous disease subtype appears to drive the disease process. There should be a high index of suspicion for ILD in SSc patients presenting with a gold mining history, dyspnoea, cough and bibasal crackles.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Internal Medicine. Johannesburg, 2014
Keywords: Lung Diseases, Interstitial; Scleroderma, Systemic